Fertilization Capacity of Rooster Spermatozoa in Response to the Modification in the Semen Composition - El-Gendy, Essam A.; Ahmed, Marwa M.; El-Tantawy, Shoukry M.; Ibrahim, Shawki A. (International Journal of Poultry Science, 2012)
An experiment was carried out to study the changes in fertilization capacity of rooster sperms in response to the modification in the biochemical composition of the semen. Chickens of two lines (CE2 and CE4) were used. Seven treatments of semen were designed and included the incubation of sperm with the plasmid, with a mixture of the plasmid and lipofectin at 2.5 or 5% concentration and the incubation of spermatozoa with lipofectin and a semen extender (BPSE). The progenies were obtained from the insemination of hens by the semen of different treatments. Sperm motility was greatly influenced by the treatments. Motility was significantly the highest in the control semen and averaged 92.42% and highly significantly declined to 52.08 and 58.75% in the semen samples treated with the plasmid, lipofectin at 2.5 or 5% concentration and diluted with BPSE. The percentage of live sperm was not affected by the addition of the plasmid. The addition of the plasmid and lipofectin or the dilutent BPSE resulted in a significant reduction in the percentage of live sperms. The percentage of live sperms was 59-62% when the plasmid, lipofectin and BPSE were all together added to the semen samples. The percentages of dead and abnormally-shaped sperm reached to 26.88 and 17.13%, respectively, in the semen treated with plasmid, lipofectin 5% and BPSE. Fertility averaged 88.22% in the eggs of hens inseminated with the control semen and significantly decreased to 42.14% when semen was incubated with the plasmid pUC18 and reached to 58.98% when semen was treated with plasmid, lipofectin (5%) and BPSE.